Exploring the Efficacy of Project-Based Learning in English Language Teaching: A Literature Review - Stenlly Sedubun; Nurhayati Nurhayati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to explore the efficacy of project-based learning (PBL) in the context of English language teaching (ELT). The study seeks to identify the benefits and challenges associated with implementing PBL in language classrooms and explores its impact on language learning outcomes. A systematic literature review of relevant academic literature was conducted, focusing on studies published between 2010 and 2023. Peer-reviewed articles, books, and conference proceedings were analyzed to synthesize current findings on applying PBL in ELT settings. The review reveals that PBL promotes meaningful language use, fosters learner autonomy, and enhances communicative competence among language learners. Students engaged in PBL demonstrate improved motivation, collaboration skills, and critical thinking abilities. However, challenges such as time constraints, assessment issues, and instructor readiness were noted as potential barriers to effective PBL implementation. Based on the findings, recommendations include comprehensive teacher training in PBL methodologies, the development of appropriate assessment strategies that align with PBL objectives, and integration of PBL activities that cater to diverse learner needs. Future research should explore PBL's long-term impact on language proficiency and investigate effective strategies for overcoming implementation challenges.